2021
DOI: 10.1159/000516610
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Xanthine Oxidoreductase Activity Associated with Glycemic Control in Patients with Pre-Dialysis Chronic Kidney Disease

Abstract: <b><i>Introduction:</i></b> Xanthine oxidoreductase (XOR) activity plays an important role as a pivotal source of reactive oxygen species, which is associated with cardiovascular disease (CVD) events. Patients with CKD have increased risk of CVD events. In the present study, factors associated with plasma XOR activity in pre-dialysis CKD patients were investigated. <b><i>Methods:</i></b> In this cross-sectional study, plasma XOR activity in 118 pre-dialysis CKD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…A correlation has been suggested between eGFR and serum XOD activity in patients with chronic kidney disease (CKD) before dialysis, as well as in obese subjects. [15] Taken together with the results of the present study, these observations suggest that, in the population with normal renal function, XOD level is higher in those with higher than lower eGFR. After oral administration of inosine, the higher XOD level in the high-eGFR group transformed the exogenous purine into urate at a faster rate.…”
Section: Discussionsupporting
confidence: 85%
“…A correlation has been suggested between eGFR and serum XOD activity in patients with chronic kidney disease (CKD) before dialysis, as well as in obese subjects. [15] Taken together with the results of the present study, these observations suggest that, in the population with normal renal function, XOD level is higher in those with higher than lower eGFR. After oral administration of inosine, the higher XOD level in the high-eGFR group transformed the exogenous purine into urate at a faster rate.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, XOR inhibition can reduce the oxidative stress related to organ damage from renal failure. A positive correlation between XOR activity and serum creatinine levels in CKD patients has been reported [30]. There was a negative correlation between XOR activity and eGFR in patients with chronic heart failure [31].…”
Section: Discussionmentioning
confidence: 79%
“…A study of 118 patients with CKD showed that estimated glomerular filtration (eGFR) and levels of HbA1c or plasma glucose were significantly, independently, and positively associated with plasma XOR activity after adjusting for several confounders; in addition, plasma XOR activity was significantly higher in diabetic CKD patients than in those without diabetes, and the relationship between glycemic control and plasma XOR activity was significant even in CKD patients without uric acid-lowering drug treatment. The findings of this study suggest that glycemic control in CKD patients in regard to decreased XOR is important and could possibly lead to a decrease in CVD events [ 65 ]. A prospective study of 101 patients with CKD or on chronic hemodialysis who were followed for up to three years showed that the serum level of XOR activity, but not UA, was an independent predictor of cardiovascular events.…”
Section: Plasma Xor Activity and Cardiovascular Events In Patients Wi...mentioning
confidence: 99%